Angiotensinergic neurotransmission in the bed nucleus of the stria terminalis is involved in cardiovascular responses to acute restraint stress in rats - Gomes-de-Souza, Lucas [UNESP]; Santana, Flávia G. [UNESP]; Duarte, Josiane O. [UNESP]; Barretto-de-Souza, Lucas [UNESP]; Crestani, Carlos C. [UNESP] (Springer Nature, 2023)
The brain angiotensin II acting via AT1 receptors is a prominent mechanism involved in physiological and behavioral responses during aversive situations. The AT2 receptor has also been implicated in stress responses, but its role was less explored. Despite these pieces of evidence, the brain sites related to control of the changes during aversive threats by the brain renin-angiotensin system (RAS) are poorly understood. The bed nucleus of the stria terminalis (BNST) is a limbic structure related to the cardiovascular responses by stress, and components of the RAS system were identified in this forebrain region. Therefore, we investigated the role of angiotensinergic neurotransmission present within the BNST acting via local AT1 and AT2 receptors in cardiovascular responses evoked by an acute session of restraint stress in rats. For this, rats were subjected to bilateral microinjection of either the angiotensin-converting enzyme inhibitor captopril, the selective AT1 receptor antagonist losartan, or the selective AT2 receptor antagonist PD123319 before they underwent the restraint stress session. We observed that BNST treatment with captopril reduced the decrease in tail skin temperature evoked by restraint stress, without affecting the pressor and tachycardic responses. Local AT2 receptor antagonism within the BNST reduced both the tachycardia and the drop in tail skin temperature during restraint. Bilateral microinjection of losartan into the BNST did not affect the restraint-evoked cardiovascular changes. Taken together, these data indicate an involvement of BNST angiotensinergic neurotransmission acting via local AT2 receptors in cardiovascular responses during stressful situations.
Keywords: Angiotensin; AT1 receptor; AT2 receptor; BNST; Captopril; Emotional stress